THE TRUE VALUES OF THE MAVLONO JALOLIDDIN MUHAMMAD RUMIY’S PHILOSOPHY IN RUSSIAN TRANSLATIONS - Mr. Babayev Otabek Abdikarimovich (Research Parks Publishing LLC, 2020)
The importance of translation and the versatility of Rumi's work, in which stories, didactic poems, and fairy tales, as well as parables and aphorisms, are combined that directly address the human element and invite him to reflect, make him a world figure of mystical poetry in which the Ontology of love and the theology of peace